A Review on Zinc Stannate Nanoparticle Based On Gas Sensor - Dr. Manisha. S. Pande, (International Journal of Scientific Research in Science and Technology, 2026)
Several types of semiconductor-based metal oxide gas sensors have been developed to meet the demands of modern life. Sensors are employed for monitoring environments in the commercial, health, and environmental categories. Researchers have been emphasizing on semiconductor-based metal oxide gas sensors types due to the numerous applications of gas sensors. Perovskite Zinc Stannate nanoparticle based on gas sensor are excellent prospects for air pollution reduction techniques, as reviewed in this research. This research concentrated on the employing of nanostructured perovskite-type semiconductor-based metal oxide gas sensors as a novel gas-sensitive material for the detection of nitrogen dioxide NO2 due to their toxic nature.
Keywords: Zinc stannate; perovskite; nanoparticle; gas sensors